INTEGRATION OF TECHNOLOGY IN ISLAMIC BOARDING SCHOOL: OPPORTUNITIES AND CHALLENGES FOR ISLAMIC EDUCATION - Wajdi, Muh Barid Nizarudin; Irsyadiah, Nur; Marlina, Yuli Marlina; Aziz, Abdullah Aminuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore the integration of technology within the pesantren ecosystem, focusing on the opportunities and challenges faced. A qualitative method was employed, utilizing interviews and observations at several pesantren in Indonesia. The findings indicate that the use of applications such as E-Santren and digital learning platforms enhances management efficiency and educational quality. However, challenges such as limited infrastructure and resistance to change remain significant barriers. Recommendations for future research include exploring the long-term impacts of technology integration and developing more inclusive models. This research provides important insights into how pesantren can adapt to technological advancements while maintaining traditional values.